Strengthening Institutional Image Through Public Communication Strategies in the Rebranding Process of the Ministry of Defense of the Republic of Indonesia - Madelyn Aurelia Adaira; Made Leni Wijayanti Panggabean; Danu Ega (COMMENTATE: Journal of Communication Management, 2026)
The image of government institutions is a critical asset in building public trust, and rebranding is one of the strategies used to strengthen it, as undertaken by the Ministry of Defense of the Republic of Indonesia (Kemhan RI) through the launch of a new logo in January 2022 to replace its identity used since 2005. This study aims to examine how public communication strategies contributed to strengthening institutional image during Kemhan RI's rebranding process, using Harold Lasswell's communication model (Who Says What In Which Channel To Whom With What Effect) as the analytical framework. A qualitative case study approach was employed, with data collected through semi-structured interviews with five purposively selected key informants, comprising senior public relations officials, military and civilian staff, an external branding expert, and an institutional intern, conducted between January and April 2024. Source and methodological triangulation were applied to ensure data trustworthiness, and data were analysed using the Miles and Huberman interactive model. The findings show that rebranding communication was carried out through a two-tier communicator structure led by the Minister of Defense and operationalised by the Public Relations Bureau, with messages grounded in seven institutional values aligned with the bureaucratic reform agenda. A multiplatform communication strategy spanning mass media, social media, and official digital channels produced measurable public engagement, including 9,610 Instagram likes and 517 Twitter engagements on the rebranding announcement. Preliminary survey data further indicate that 93% of respondents assessed Kemhan RI's image as having improved following the rebranding. The study concludes that successful government rebranding depends not on visual change alone but on the strategic coherence of its accompanying communication process, contributing theoretically by advancing a more dynamic application of Lasswell's model as a framework for evaluating strategic communication coherence in institutional contexts.